Fall Prevention: Staying Active - Sergio Romero; Linda B. Bobroff (EDIS)
Exercises that improve your balance, flexibility, and strength can reduce your risk for falls. This revised 4-page fact sheet describes exercises that can help you maintain or improve your balance, strength, and flexibility. Written by Sergio Romero and Linda B. Bobroff and published by the UF Department of Family Youth and Community Sciences, May 2011.